An outcome of expert-oriented digitalization of university processes - Altti Lagstedt; Juha P. Lindstedt; Raine Kauppinen (Springer, 2022)
Digitalization challenges the way in which business processes are seen. The potential for enhancement is even recognized in business areas that traditionally have little to do with IT. Even though universities have long-standing traditions of how work is organized, they have not been eager to adopt digitalized processes. Because core university processes rely on highly skilled experts, digitalizing processes are not as straightforward as they would be in more mechanical work. We developed an expert-oriented digitalization model (EXOD) for the digitalization of university processes and tested it using a case study. After digitalizing a core process, we interviewed the experts involved. The results show the usefulness and adaptability of the model. Based on the results, we recommend further studies to refine and test the model more comprehensively. In addition, based on the adaptability of the model, we recommend it as a baseline for university process digitalization projects in general.